Light and temperature records of the seawater associated with southern elephant seal dives during foraging trips in South Atlantic and Pacific Oceans - Eder, Elena Beatriz; Zárate, Marcos Daniel; Lewis, Mirtha Noemi (Biodiversity Data Journal)
The dataset encloses geolocalized records of dive and surface interval durations, light level and temperature of the seawater during the postresting and postmolting trackings of 13 immature southern elephant seals, Mirounga leonina. It describes an unpublished open access version of the original data with records of light level and temperature of the water column using the Darwin Core standard (DwC) through ArOBIS guaranteeing compliance with the FAIR principles, encompassing a wide time scale (2005, 2006 and 2007) and geographic range in the South Atlantic and Pacific Oceans (South West [-58.75, -81.29], North East [-37.60, -28.65]). Seals were simultaneously equipped with affordable light–temperature loggers (LTLs) and satellite devices. The LTLs recorded light level and temperature of the water column at 30-s intervals during dives, and light–time records were applied to estimate dive parameters of diurnal records from 06:00 am to 05:00 pm, since movements up and down the water column are reflected by changes in light level. For that, the minimum light level reached at the surface of a dive was determined experimentally with diurnal dive simulations at sea using the LTLs devices before deployment. The dataset also includes variation of light and temperature of records between 17 pm to 06:00 am. Data can be used to identify temperature changes associated to seawater masses as drivers of the distribution of other taxa of interest, and variation of light level in the seawater (light attenuation) could be linked to concentrations of phytoplankton assemblages as an index of primary productivity.This dataset provides unpublished primary data of the duration of dives and surface intervals, and associated records of light level and temperature variations along the movements throughout the sea water of 13 immature southern elephant seals in the southern Hemisphere. Data were recorded with light-temperature loggers (LTLs) and uploaded following the Darwin Core standard and compliance with the FAIR principles. Fil: ...